PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN PRODUKSI PT.MEUBELINDO SEMARANG - Gilang Gumilang; Saryadi Saryadi; Wahyu Hidayat (Jurnal Ilmu Administrasi Bisnis, 2013)
PT. Meubelindo Semarang is a manufacturing company engaged in the manufacture of furniture, products manufactured by PT.Meubelindo is kind of teak garden furniture. As a company engaged in production activities, motivation and the work environment is important to the company. The research was motivated by the last four years of production data from the PT. Meubelindo Semarang has decreased and has not reached the specified targets. This study aimed to determine how much effect the motivation and the work environment on productivity. This study used explanations research using questionnaire as the instrument which distributed to 70 production employees of PT. Meubelindo Semarang. The results of the analysis prove that the motivation variable t value (6.876)> t table (1.9955) which means Ha received thus no significant effect between motivation and productivity of employees with the close relationship of 0.410. In the work environment variables t count (3.577)> t table (1.9955) which means Ha accepted, thus no significant effect between the work environment on employee productivity with the closeness of the relationship 0.158. While jointly acquired F calculation (32.519)> F table (3.1296) which indicates that the Ha accepted that hypothesis proved that there was an effect between the variables of motivation and the work environment on employee productivity, with the closeness of 0.493.